2013
DOI: 10.3892/mco.2013.233
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of type XXII and XXIV collagen mRNA expression in head and neck cancer patients

Abstract: Abstract. Squamous cell carcinoma of the head and neck (HNSCC) is the sixth most common type of cancer, affecting ~500,000 individuals worldwide annually. Collagen is the major constituent of the extracellular matrix component in tumors and plays a crucial role in tumor development. The aim of this study was to determine the mRNA expression of type XXI, XXII, XXIII and XXIV α1 collagen (COL21A1, COL22A1, COL23A1 and COL24A1, respectively) in head and neck squamous cell carcinoma (HNSCC) and investigate its cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 23 publications
(28 reference statements)
2
30
0
Order By: Relevance
“…Head and neck carcinoma is the sixth most common cancer worldwide and about 95% of them are squamous cell carcinoma (SCC) which is still a significant cause of death in the world and this disease affects nearly 500,000 patients annually worldwide . The possible factors for causing oral cancer include environment, nutritional deficiencies, consumptions of alcoholic products, tobacco smoking, betel quid chewing, and papillomaviruses infection .…”
Section: Introductionmentioning
confidence: 99%
“…Head and neck carcinoma is the sixth most common cancer worldwide and about 95% of them are squamous cell carcinoma (SCC) which is still a significant cause of death in the world and this disease affects nearly 500,000 patients annually worldwide . The possible factors for causing oral cancer include environment, nutritional deficiencies, consumptions of alcoholic products, tobacco smoking, betel quid chewing, and papillomaviruses infection .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, degradation of collagen type XVIII resulting in the formation of endostatin causes inhibition of angiogenesis and thereby retards tumour growth [ 43 ]. Furthermore, some collagens such as type XXII and XXIV have been referred to have prognostic value in certain cancers [ 44 ].…”
Section: Reviewmentioning
confidence: 99%
“…5,6 Collagen is also the main component of the tumor extracellular matrix, and it plays an important role in the development of tumors. 7,8 Many studies have investigated the collagen family in HCC. Hepatocellular carcinoma is primarily associated with cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…15 In addition, Dr. Kiyoshi has demonstrated that the overexpression of the COL24A1 gene may be a valuable biomarker for prognosis in HNSCC. 7 Certain markers, such as AFP, 16 AFP-L3, 17 GCP3, 18 and MDK, 19 have often been used in HCC diagnosis. Nevertheless, most of these markers are unlikely to exactly reflect the diagnostic and therapeutic efficiency.…”
Section: Introductionmentioning
confidence: 99%